Factors influencing development of the infant microbiota: from prenatal period to early infancy - Sujin Jeong (The Korean Pediatric Society, 2022)
During early life, the gut microbial composition rapidly changes by maternal microbiota composition, delivery mode, infant feeding mode, antibiotic usage, and various environmental factors, such as the presence of pets and siblings. An integrative study on the diet, the microbiota, and genomic activity at the transcriptomic level may give an insight into the role of diet in shaping the human/microbiome relationship. Disruption in the gut microbiota (i.e., gut dysbiosis) has been linked to necrotizing enterocolitis in infancy, as well as some chronic diseases in later, including obesity, diabetes, inflammatory bowel disease, cancer, allergies, and asthma. Therefore, understanding the impact of maternal-to-infant transfer of dysbiotic microbes and then modifying infant early colonization or correcting early-life gut dysbiosis might be a potential strategy to overcome chronic health conditions.